Integrating the Competing Values Framework and Social Identity Theory: A Systematic Literature Review of CSR–OCB Mechanisms - Mentari Clara Dewanti; Virginia Mandasari (Universitas Pendidikan Ganesha, 2026)
This systematic literature review synthesizes empirical and conceptual evidence from 2018 to 2025 on the interrelationships among organizational culture, Corporate Social Responsibility (CSR), and Organizational Citizenship Behavior (OCB), addressing a critical gap in prior research that has largely examined these constructs in isolation or through fragmented theoretical perspectives. Utilizing the Competing Values Framework (CVF) and Social Identity Theory (SIT) as guiding lenses, the review identifies how cultural orientations—clan, adhocracy, market, and hierarchy—shape distinct expressions of OCB and how CSR functions as a mediating mechanism translating cultural values into discretionary employee behaviors. The review analyzed 42 peer-reviewed studies across Asia, Europe, and North America, a corpus sufficient to capture recent theoretical and methodological developments and reflect the growing scholarly integration of cultural, social responsibility, and identity-based perspectives in explaining employee citizenship behavior. The findings demonstrate that OCB emerges from the synergistic interaction between organizational culture and CSR, mediated by identity-based processes, advancing existing literature by integrating structural cultural typologies with psychological identification mechanisms into a unified explanatory framework. This review contributes a theoretically grounded synthesis that clarifies CSR’s dual role as both a reflection of cultural value orientations and a catalyst for identity-driven discretionary behavior, thereby informing the strategic alignment of CSR with organizational culture to cultivate sustainable citizenship behaviors and providing a foundation for future empirical investigations across diverse industrial and cultural settings.